Pengaruh Kualitas Pelayanan Terhadap Kepuasan Siswa Di Lembaga Pendidikan Smartfast Global Education Pekanbaru - Hikmatul , Wardiani; Abdul, Aziz (Eko dan Bisnis: Riau Economic and Business Review, 2025)
This research aims to determine the effect of service quality on student satisfaction at the Smart Fast Gobal Education Education Institution. The data analysis technique used is simple regression analysis. Hypothesis testing with the t test shows that there is a t count of 6.854, which means that from the t table it is obtained that the t table is 1.995, so the hypothesis test for this research is t table 6.854 > t count of 1.995, which means that service quality has a significant effect on student satisfaction at Smart Fast Global Education Pekanbaru. The relationship between service quality (X) and job satisfaction (Y) is positive as evidenced by the results of b = 0.498, which means that for every one unit increase in service quality, Smart Fast Global Education Pekanbaru student satisfaction will be increased by 0.498 units. The contribution of service quality to Smart Fast Global Education Pekanbaru student satisfaction is 40.90%